2007
DOI: 10.2135/cropsci2006.02.0063
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Roundup Ready Flex Cotton, ‘MON 88913’, for Use in Ecological Risk Assessment: Evaluation of Seed Germination, Vegetative and Reproductive Growth, and Ecological Interactions

Abstract: Biological and ecological data collected on a genetically modified crop and an appropriate control are useful for assessing potential ecological risk. Specific characteristics studied are selected on the basis of relevance to potential ecological effects, are well known, and are accepted by plant breeders. In these studies, germination, vegetative and reproductive growth, or ecological characteristics of Roundup Ready Flex cotton, MON 88913 were compared with a negative control, MON 88913(‐). Statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Both the US and Japan rely on the concept of familiarity (Horak et al 2007 , 2015 ) when interpreting statistical differences identified between the GM crop and a conventional control in confined field trials. As described by the Organisation for Economic Co-operation and Development (OECD), familiarity is a concept coming from the knowledge and experience gained over time (Nickson and Horak 2006 ; OECD 1993 ).…”
Section: Purpose Of Confined Field Trial Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the US and Japan rely on the concept of familiarity (Horak et al 2007 , 2015 ) when interpreting statistical differences identified between the GM crop and a conventional control in confined field trials. As described by the Organisation for Economic Co-operation and Development (OECD), familiarity is a concept coming from the knowledge and experience gained over time (Nickson and Horak 2006 ; OECD 1993 ).…”
Section: Purpose Of Confined Field Trial Assessmentmentioning
confidence: 99%
“…In the US, data from GM crops and non-GM controls are compared at a single location (pollen study) or across locations (germination study and growth and development studies) (Steps 1 and 2 in Fig. 1 ) as the initial steps (Horak et al 2007 , 2015 ). If a statistically significant difference between the GM crops and non-GM controls is detected, the mean value of GM crop is compared with the range of means obtained for the reference varieties grown in that study (Step 3 in Fig.…”
Section: Reliability Of the Confined Field Trial Data Obtained In Culmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic and agronomic characterization of GM crops relative to conventional crops provides a comparative context that is used within the natural variation of the crop to establish “familiarity” (Nickson and Horak 2006). Ultimately, this comparative assessment is used to assess potential risks that may be hypothesized regarding the cultivation of GM crops (Horak et al 2007, 2015; Raybould et al 2012; Sammons et al 2014) and that are assessed on the basis of specific environmental protection goals (Nickson 2008). The concept of familiarity is useful to decision makers and regulators because it comes from preexisting general knowledge of the biology and agronomic characteristics of a crop, previous field cultivation results, expert opinions, historical agronomic experience, and the characteristics of the trait(s) introduced, the receiving environment, and their interactions (Nickson and Horak 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A weight of evidence from field studies of GM crops in uncultivated land (e.g., Crawley et al 1993 ; 2001 ), phenotypic comparisons of GM crops with non-GM near isolines (e.g., Horak et al 2007 ), and molecular analysis of genetic changes induced by transformation and other breeding methods (e.g., Ricroch et al 2011 ) suggests that GM crops are no more likely to be serious weeds than are other new crop varieties. Nevertheless, new data are often required to complete regulatory assessments of the weediness and invasiveness of GM crops (e.g., Raybould et al 2012 ).…”
mentioning
confidence: 99%